Carbon Emissions and Economic Drivers in Kalimantan: New Evidence from ARDL Bounds Testing - Puah, Chin-Hong; Jong, Meng-Chang; Roslinda, Emi (International Journal of Energy Economics and Policy, 2026)
This study investigates how deforestation, economic growth, and trade openness affect carbon emissions in Kalimantan, Indonesian by using the Environmental Kuznets Curve (EKC) framework. The present study applies the ARDL bounds testing approach with quarterly data spanning from 2015Q1 to 2024Q4. The results show that all three selected parameters are significantly influence carbon emissions in Kalimantan. Deforestation increases emissions, while higher income and greater trade openness reduce carbon emissions. The findings show an inverted U-shaped relationship between income, trade openness, and carbon emissions, confirming the EKC hypothesis is valid in the present study. Environmental degradation rises in the early growth phase but declines once income reached a certain threshold level. The study also finds that cleaner energy and foreign direct investment (FDI) are crucial for improving environmental quality. Trade openness attracts FDI, boosts productivity, and supports advanced technology shared by the importing countries. The empirical outcomes suggest that the government can promote adoption of green technology, sustainable land use, and international trade cooperation between the countries. Strengthening global collaboration helps accelerate technology transfer and reduce environmental harm to the nation. These efforts align with the Sustainable Development Goals (SDGs) to combat the climate change for the long-term sustainability growth. This paper contributes to the limited literature on how deforestation, income and trade openness in reducing carbon emissions in Kalimantan.